Modified mechanical mass-spring model of biomolecules for understanding dynamics of proteins - Eom, Kilho; Ahn, Jeong-Hee; Kim, Jae-In; Yoon, Gwon-Chan; Na, Sungsoo (KOREAN SOC MECHANICAL ENGINEERS, 2008)
A dynamic model applicable to biomolecular structures for understanding the dynamics and the vibrational behaviors of protein is considered. A mechanical mass-spring model represented by point masses and harmonic springs is presented. The biomolecular structure may be envisioned by a mass and spring system with multi-degrees-of-freedom because dominant atoms in protein may be considered to be point masses, and bonding and non-bonding interactions between atoms of interest and surrounding atoms within some critical distances are implemented by a spring. Furthermore, a model condensation scheme is to be introduced because most proteins have large degree of freedom requiring large computation time and memory, which results in reducing computational cost and maintaining the accurate predictions. From solving the corresponding eigenvalue problem constructed from a multi-degree-of-freedom system, our results show the modified mechanical spring-mass model of a biostructure through a condensation scheme is very successful in predicting the dynamics of molecular structures in terms of thermal fluctuations and eigenmode, etc.
Keywords: MOTIONS